Multi-lingual Research in Minority-majority Communities - Debra Bolton (Adult Education Research Conference, 2015)
: Reaching under-served audiences can be a challenge when we lack knowledge of needs. Using data to create relevant educational topics support adult educators for student success. This study addresses well-being and social connectedness in multi-lingual, Minority-majority, rural communities, and compares data in similar studies that used an English-only approach.
Keywords: multi-lingual research; well-being; social connectedness